Environmental isotopes applied to the evaluation and quantification of evaporation processes in wetlands: a case study in the Ajó Coastal Plain wetland, Argentina - Carol, Eleonora Silvina (2015)
In the Ajó coastal plain, which occurs in the south of the Samborombón Bay, Argentina, certain sectors of the wetland are influenced by the tidal flow, whereas others are not. In the tidally restricted Ajó wetlands, the evapotranspiration process is one of the most important components of the water balance due to fact that the flat morphology and low soil permeability make the flow of surface and groundwater difficult. Although evaporation is an important component of evapotranspiration, a quantitative estimation of this process is still lacking or poorly known. In this work, we quantify the evaporation term in the tidally restricted wetlands by applying isotopic modelling and assessing the hydrological response of the wetland by means of other methodologies, such as satellite imaging and level measurements. The results show that during deficit periods, the total evaporation ranges between 10 and 33 % of the local precipitation. In groundwater samples, it fluctuates between 2 and 13 %, whereas in surface water it varies between 8 and 20 %. Analyses of the water budget, satellite images and water level time series provide evidence on how evaporation processes regulate the hydrology of the wetland. The water balance suggests the occurrence of a deficit period, in which the satellite images show a reduction of the waterlogged areas and lakes, and a lowering in surface and groundwater level is recorded.